Economic evaluation of long-life pavements. (Transport (Paris, France), 2005)
With maintenance costs accounting for a large proportion of road budgets, this report assesses the economic and technical feasibility of innovative wearing courses for long life road pavements. (The wearing course is the top layer of a pavement structure which provides the riding surface for vehicles.) While having higher initial costs, such wearing courses have the potential to dramatically reduce recurrent road maintenance requirements and user costs and could also reduce overall costs significantly, under circumstances outlined in the report.--Publisher's description.